2014
DOI: 10.14257/ijmue.2014.9.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Managed Optical Links with Optical Phase Conjugator Placed at the Various Positions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…It had been confirmed that the optimal NRD controlled by pre-concentrated compensation was resulted to 10 ps/nm, regardless of the SMF length, RDPS, launch power, dispersion coefficient [14,15]. This result is remarkably consistent with the result of Reference [13] by Xiao's research dealing with "pseudolinear" system.…”
Section: Modeling Of Wdm Transmission System and Numerical Assessmentsupporting
confidence: 80%
See 1 more Smart Citation
“…It had been confirmed that the optimal NRD controlled by pre-concentrated compensation was resulted to 10 ps/nm, regardless of the SMF length, RDPS, launch power, dispersion coefficient [14,15]. This result is remarkably consistent with the result of Reference [13] by Xiao's research dealing with "pseudolinear" system.…”
Section: Modeling Of Wdm Transmission System and Numerical Assessmentsupporting
confidence: 80%
“…Authors have confirmed through the previous studies that the DCF's position with respect to the SMF in the fiber spans before OPC and after OPC should be opposite to each other for the symmetric distribution of the local dispersion in the optical links with DM and optical phase conjugation [14][15]. That is, if the compensation scheme is precompensation before OPC, then post-compensation will be applied into the fiber spans after OPC for effective compensation, especially the distorted WDM signals.…”
Section: Introductionmentioning
confidence: 88%